Synthesis, Characterization and Studies on Catalytic Behavior of Mn(?) Complex with 2, 2? Bipyridine, 1, 1? Dioxide Ligand within Nanoreactors of MCM-41 (Journal of Sciences, Islamic Republic of Iran)
Manganese (?) complex with 2, 2? bipyridine, 1, 1? dioxide (bpdo) ligand was immobilized within nanoreactors of MCM-41. The immobilized complex was characterized by powder x-ray diffraction (XRD), nitrogen adsorption desorption, and FTIR. The pore volume, surface area and pore diameter of MCM-41 decreased after immobilization of Mn complex. Three bands observed at 1250, 1220 cm?1 and 757 cm?1 are attributed to the NO stretching and bending vibrations respectively. It was found that the immobilized Mn complex on MCM-41 successfully catalyzed the oxidation of cyclohexene, styrene, norbornene, and trans-stilbene with tert-butylhydroperoxide (TBHP).With the exception of cyclo-hexene, the other three olefins afforded the corresponding epoxides efficiently. Preparation and catalytic effect of Mn salt either on MCM-41 or modified MCM-41 with aminopropyltriethoxysilane; MCM-41(AP) will be discussed.